Literature review of waste management strategies in industry - Suquisupa Villacis, Anderson; Morales Núñez, Milena; Parrales León, Aldo; Morante-Galarza, Marianela (EASI: Engineering and Applied Sciences in Industry, 2023)
Waste management strategies to provide sustainable solutions in industry processes to accomplish current regulations are crucial in industrial engineering. The general objective of this study was to summarize waste management practices in industrial plants by applying a systematic mapping of literature in citation databases (Redalyc, Scopus, and Web of Science). First, a scoping review led the process to determine current waste management practices in industrial plants. The analysis of hazardous waste management practices includes minimization, recycling, and reuse. The general approach is focused on the facilities to promote safe waste storage, transport, and final disposal.
Keywords: waste; management; circular economy; environmental